2023
DOI: 10.3390/nu15133055
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the Ideal Probiotic Healing Regime

Abstract: Wound healing is a multi-factorial response to tissue injury, aiming to restore tissue continuity. Numerous recent experimental and clinical studies clearly indicate that probiotics are applied topically to promote the wound-healing process. However, the precise mechanism by which they contribute to healing is not yet clear. Each strain appears to exert a distinctive, even multi-factorial action on different phases of the healing process. Given that a multi-probiotic formula exerts better results than a single… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
(156 reference statements)
0
2
0
Order By: Relevance
“…At the same time, there are quite a lot of clinical studies referring to the reduction in postoperative bloating and the shortening of the time duration up to the first flatus, all indirectly indicating the shortening of the postoperative paralytic ileus [118][119][120]. Both the above [115][116][117][118][119][120] may not have a direct, suppressive effect on the pain originating from abdominal wall trauma, or from the distension of the gut wall, but there are many studies documenting the specific cytokine and other molecular changes which point in that direction.…”
Section: Probiotics In Postoperative Pain Managementmentioning
confidence: 96%
See 2 more Smart Citations
“…At the same time, there are quite a lot of clinical studies referring to the reduction in postoperative bloating and the shortening of the time duration up to the first flatus, all indirectly indicating the shortening of the postoperative paralytic ileus [118][119][120]. Both the above [115][116][117][118][119][120] may not have a direct, suppressive effect on the pain originating from abdominal wall trauma, or from the distension of the gut wall, but there are many studies documenting the specific cytokine and other molecular changes which point in that direction.…”
Section: Probiotics In Postoperative Pain Managementmentioning
confidence: 96%
“…According to the current definition, "probiotics are live microorganisms that, when administered in adequate amounts, confer a health effect on the host" [114]. Today, many in vitro and in vivo studies have shown that probiotics exert potential suppressive effects on various infectious and inflammatory conditions, thus significantly shortening the inflammatory phase of the wound healing process [115][116][117]. At the same time, there are quite a lot of clinical studies referring to the reduction in postoperative bloating and the shortening of the time duration up to the first flatus, all indirectly indicating the shortening of the postoperative paralytic ileus [118][119][120].…”
Section: Probiotics In Postoperative Pain Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…168 The use of smart hydrogels encapsulated with microorganisms is a popular strategy among researchers. 169 Chlorella vulgaris is an alga that can produce O 2 through photosynthesis, which researchers hope can be used as an exogenous O 2 release agent for diabetic wounds. However, its proliferation may be interfered with the proliferation of diabetic wound bacteria.…”
Section: Smart Hydrogels For Wound Therapymentioning
confidence: 99%
“…Probiotics could also impact, at least indirectly, the proliferative phase, stimulating the re-epithelialization and neovascularization of the damaged tissue. The presence of probiotics leads to the stimulation of the pro-inflammatory M1 macrophage phenotype, followed by the immediate switch to M2, an anti-inflammatory response that promotes angiogenesis and epithelization [ 60 ]. If initially a pro-inflammatory response is necessary for microbial sterilization and the removal of foreign compounds, in the second phase of the healing process, a regression of neutrophils and macrophages is necessary to allow the scar to heal.…”
Section: Mechanisms Of Probiotics In Wound Healingmentioning
confidence: 99%